Experimental characterization of magnetically focused electron contamination at the surface of a high‐field inline MRI‐linac. Issue 12 (21st October 2019) - Roberts, Natalia F.; Patterson, Elizabeth; Jelen, Urszula; Causer, Trent; Holloway, Lois; Liney, Gary; Lerch, Michael; Rosenfeld, Anatoly B.; Cutajar, Dean; Oborn, Bradley M.; Metcalfe, Peter
Abstract : Purpose: The fringe field of the Australian MRI‐linac causes contaminant electrons to be focused along the central axis resulting in a high surface dose. This work aims to characterize this effect using Gafchromic film and high‐resolution detectors, MO Skin TM and microDiamond. The secondary aim is to investigate the influence of the inline magnetic field on the relative dose response of these detectors. Methods: The Australian MRI‐linac has the unique feature that the linac is mounted on rails allowing for measurements to be performed at different magnetic field strengths while maintaining a constant source‐to‐surface distance (SSD). Percentage depth doses (PDD) were collected at SSD 1.82 m in a solid water phantom positioned in a low magnetic field region and then at isocenter of the MRI where the magnetic field is 1 T. Measurements for a range of field sizes were taken with the MO Skin TM, microDiamond, and Gafchromic ® EBT3 film. The detectors' relative responses at 1 T were compared to the near 0 T PDD beyond the region of electron contamination, that is, 20 mm depth. The near surface measurements inside the MRI bore were compared among the different detectors. Results: Skin dose in the MRI, as measured with the MO Skin TM, was 104.5% for 2.1 × 1.9 cm 2, 185.6% for 6.1 × 5.8 cm 2, 369.1% for 11.8 × 11.5 cm 2, and 711.1% for 23.5 × 23 cm 2 . The detector measurements beyond the electron contamination region showed agreement between the relative response at 1 T and near 0 T. Film was in agreement with both detectors in this region further demonstrating their relative response is unaffected by the magnetic field. Conclusions: Experimental characterization of the high electron contamination at the surface was performed for a range of field sizes. The relative response of MO Skin TM and microDiamond detectors, beyond the electron contamination region, were confirmed to be unaffected by the 1‐T inline magnetic field.